Penerapan AI dalam Pembelajaran untuk Meningkatkan Kualitas Pendidikan di SMAN 3 Bukitinggi - Kurnia Mira Lestari; Supratman Zakir; Ramadhoni Aulia Gusli (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The basis of this research is that, despite advances in the world, including the development of technology and artificial intelligence at SMA Negeri 3 Bukittinggi, educators are unable to use these tools and often deliver content in traditional ways. To improve the quality of education for students, teachers, and SMA Negeri 3 Bukittinggi, the school must keep up with the development of technology and artificial intelligence. This is a challenge for SMA Negeri 3 Bukittinggi to develop, so it is very important for schools to apply technology and artificial intelligence (AI) in the teaching and learning process. The research approach used in this research is qualitative research, which includes observation, interviews, field observations, and searching for research data on previous research publications that are in accordance with the topic that the researcher raises. The findings of this research show that educational institutions have felt the impact of technological advances and artificial intelligence (AI) and have utilized it to improve the teaching and learning process. One of the many conveniences and advantages of using AI is to make it easier for teachers and improve education standards. To improve education standards successfully and efficiently, education workers are finding that technological advancements and artificial intelligence are helpful in the teaching and learning process.